Legal Aspects of the Notary's Role in Protecting Parties from Substantial Errors in Making Authentic Deeds - Fadhliana, Shella; Hadi Prayitno, Ahmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
A notary is a public official who is appointed by the Government and then given the authority to serve the public in carrying out agreements and making and validating authentic deeds in a professional manner before the parties. However, if a Notary makes a writing error in an authentic deed, there will be a change in the meaning of the substance of the deed so that it becomes a source of lawsuits in the future by the parties who feel aggrieved. The method in this research is normative juridical. Juridical approach to law is seen as a norm called das sollen, because in this study it uses written legal materials in the form of a statute. The normative approach which analyzes the problem using legal materials with data obtained comes from document studies in the form of decisions and several scientific journals to analyze legal aspects and responsibilities of the role of a notary in protecting the parties for substantive errors in making authentic deeds. The research results obtained are: Notary formal aspects regarding criminal cases when making a letter that is not in accordance with legal actions, and using fake or falsified letters a Notary can be entangled in criminal law in Article 263 paragraph (1) and paragraph (2 ) of the Criminal Code . Responsibility is an obligation for public officials for authentic deeds made before the parties as regulated by Law Number 02 of 2014 concerning Notary Officer and using fake or falsified letters a Notary can be entangled in criminal law in Article 263 paragraph (1) and paragraph (2) of the Criminal Code. Responsibility is an obligation for public officials for authentic deeds made before the parties as regulated by Law Number 02 of 2014 concerning Notary Offices and using fake or falsified letters a Notary can be entangled in criminal law in Article 263 paragraph (1) and paragraph (2) of the Criminal Code. Responsibility is an obligation for public officials for authentic deeds made before the parties as regulated by Law Number 02 of 2014 concerning Notary Offices. Keywords: Authentic; Mistakes; Parties; Protection; Substance.